DISTRIBUTION OF CARBON MONIXIDE IN ALMATY CITY DEPENDING ON THE DISTANCE FROM THERMAL POWER PLANTS - 2: DISTRIBUTION OF CARBON MONIXIDE IN ALMATY CITY DEPENDING ON THE DISTANCE FROM THERMAL POWER PLANTS - 2 - Daulbayeva, Almira; Filipova, Margarita (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In recent years, according to experts, the emissions change clearly shows that urban air pollution has increased as a whole, as opposed to an overall emissions reduction in countries. In hundreds of cities of the world average air pollution levels exceed the sanitary standards. So in Almaty city thermal power plants are the largest stationary sources that contribute to air pollution. The article deals with laws of modern spatial and temporal distribution of carbon monoxide in the air basin of Almaty city, depending on the distance from TPP – 2 (thermal power plants). In particular, research shows that there is a direct relationship between the level of air pollution and wind conditions of the city.